MENINGKATKAN KETERAMPILAN PROSES SAINS SISWA KELAS IV MENGGUNAKAN MODEL GUIDED DISCOVERY LEARNING PADA MUATAN IPA DI SD NEGERI 64/1 MUARA BULIAN - Angelina Fitri Natania Sirait; Faizal Chan; Hendra Budiono (Jurnal Tunas Pendidikan, 2024)
This study aims to describe the Improvement 0f Students' Science Process Skills Using the Guided Discovery Learning Model on Science Content in Elementary Schools. Classroom action research conducted in two cycles where each cycle is carried out twice a meeting and consists of four stages namely planning, implementation, observation and reflection. The subjects of this study were students of class IV A SDN 64/1 Muara Bulian with 27 students consisting of 11 boys and 16 girls. Data collection techniques in this study were observation and documentation. The observation instruments of this research are student science process skills observation sheets and teacher activity observation sheets in each cycle. The data analysis techniques used were qualitative and quantitative. The results showed that there was an increase in the science process skills of students in class IV Elementary School, which can be seen from the results of student observations in cycle 1 with a percentage of success of 67.6% and cycle 2 with a percentage of success of 82.9%. Based on the results of the study, it can be concluded that there is an increase in students' science process skills in science learning content after the action of applying the GDL (guided discovery learning) model.